A philosophical approach to decision-making for sterilising mentally disordered adults / Wang Min Yen - Wang, Min Yen (2009)
The issue of sterilisation of mentally disordered persons has never been considered by the courts or the legislature of Malaysia. This thesis examines how the law of tort of Malaysia should look at sterilisation of mentally disordered adults. In this connection, the history of compulsory sterilisation in other jurisdictions, the way the existing legislative framework of Malaysia views the question of consent and medical treatment, as well as how the sterilisation cases in England, Canada, Australia, New Zealand and the US have developed are all looked into with a view of forming a legal proposition using a philosophical approach. It is proposed that the best interests test is not necessarily the best test and that it could be overly dependent on the value system of the decision-maker. Many of the factors that are considered important to the best interests test may not have good basis for comparison and they have contributed to the medicalisation of many legal and ethical issues. The principle of autonomy and the principle that non-therapeutic sterilisation can never be performed without the consent of the patient are the two principles that should be used to safeguard the interests of the mentally disordered adults. These two principles are used to propose a set of guiding principle for decision-makers in Malaysia after taking into consideration the existing regulatory conditions in Malaysia.